Advanced Aluminium Composites and Alloys - Dobrzański, Leszek A. (IntechOpen, 2021)
Aluminium is an engineering material of strategic importance in the current stage of Industry 4.0. This book discusses advanced composites based on aluminium alloys. It also describes pressure infiltration of gas with liquid aluminium, the mechanical synthesis of aluminium alloy powder and halloysite nanotubes (HNTs) or multi-wall carbon nanotubes (MWCNTs) consolidated by plastic deformation, selected optimization and prediction models, casting aluminium alloys containing zirconium, aluminium alloys subjected to high-speed extrusion of shapes, corrosion resistance of alloys containing lithium, machining conditions of alloys with copper and zinc additions, and more.